NON-COMPETITION CLAUSE: BUSINESS PROTECTION OR LIMITATION OF WORKER RIGHTS - Alexandra Kyra Trisno; Ratna Artha Windari; I Gusti Ayu Apsari Hadi (Universitas Pendidikan Ganesha, 2026)
This research analyses the legal validity and limitations of non-competition clauses in employment contracts under Indonesian law, focusing on their position between business protection and workers’ constitutional rights. In Indonesian legal doctrine, employment relationships are based on elements of work, wages, and subordination as regulated in Law Number 13 of 2003 concerning Manpower. From a civil law perspective, non-competition clauses fall within contractual obligations under Indonesian Civil Code, particularly Article 1234 concerning the obligation “not to do something” and Article 1320 on the validity requirements of agreements. Using normative legal research with conceptual and comparative approaches, this study analyses statute regulations, legal doctrines, and comparative practices in Singapore, Malaysia, and the United States. The findings indicate that non-competition clauses are legally permissible in Indonesia provided they fulfil subjective and objective contractual requirements, including consent, capacity, specific object, and lawful cause. However, contractual freedom is limited by constitutional guarantees, particularly Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which protects the right to work and earn a decent living. Comparatively, Singapore applies proportionality and legitimate interest tests, Malaysia generally voids post-employment non-compete clauses; and the United States adopts a state-based reasonableness This research analyses the legal validity and limitations of non-competition clauses in employment contracts under Indonesian law, focusing on their position between business protection and workers’ constitutional rights. In Indonesian legal doctrine, employment relationships are based on elements of work, wages, and subordination as regulated in Law Number 13 of 2003 concerning Manpower. From a civil law perspective, non-competition clauses fall within contractual obligations under Indonesian Civil Code, particularly Article 1234 concerning the obligation “not to do something” and Article 1320 on the validity requirements of agreements. Using normative legal research with conceptual and comparative approaches, this study analyses statute regulations, legal doctrines, and comparative practices in Singapore, Malaysia, and the United States. The findings indicate that non-competition clauses are legally permissible in Indonesia provided they fulfil subjective and objective contractual requirements, including consent, capacity, specific object, and lawful cause. However, contractual freedom is limited by constitutional guarantees, particularly Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which protects the right to work and earn a decent living. Comparatively, Singapore applies proportionality and legitimate interest tests, Malaysia generally voids post-employment non-compete clauses; and the United States adopts a state-based reasonableness approach. Indonesia occupies a middle position, relying on general contract principles and constitutional safeguards without specific statutory regulation. The study concludes that non-competition clauses may function as legitimate business protection instruments only if drafted proportionally, with clear limitations on duration, territory, and scope, while respecting workers’ fundamental rights.